KONSUMSI MAKANAN KECIL DI PAGI HARI MEMPENGARUHI MORNING SICKNESS PADA IBU HAMIL TRIMESTER PERTAMA DI WILAYAH KERJA BPS IDA AYU DESA BECIRONGENGOR SIDOARJO - Farida Umamah (Universitas Nahdlatul Ulama Surabaya, 2014)
The purpose of this study is to analyze relationship between snack consumption in the morning with morning sickness level at pregnancy mother in first trimester in working area of Private Practical Midwife (PPM) Ida Ayu Becirongengor Sidoarjo. The purpose of this study is to analyze relationship between snack consumption in the morning with morning sickness level at pregnancy mother in first trimester in working area of Private Practical Midwife (PPM) Ida Ayu Becirongengor Sidoarjo. Design study is analytic with cross sectional approach, the population were all pregnancy mother in first trimester in working area of Private Practical Midwife (PPM) Ida Ayu Becirongengor Sidoarjo with amount 30 person. Sample were 28 respondents, taken by simple random sampling technique. Independents Variable was snack consumption in the morning with morning, dependent were morning sickness level. Data were taken by using questioner and analysed using Rank Spearman test with significance level α = 0,05. Result study show that most of respondents (70,4%) consuming snack consumption in the morning, and most of them (67,9%) had mild morning sickness level. Result of Rank Spearman test got = 0,004 (α = 0,05) means there is relationship between snack consumption in the morning with morning sickness level. It’s conclusion is consuming snack in the morning can help to reduce symptoms of nausea and vomits. So, suggested to all pregnant mother have more desirable to find same more information about the pregnancies, specially consuming snack in the morning to be the main alternative handling morning sickness.